2019
DOI: 10.4491/eer.2019.419
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring of particulate hazardous air pollutants and affecting factors in the largest industrial area in South Korea: The Sihwa-Banwol complex

Abstract: Ambient air monitoring of particulate hazardous air pollutants was performed from 2005 to 2007 in the Sihwa-Banwol industrial complexes, which is the largest industrial area in Korea. The occurrence of polycyclic aromatic hydrocarbons (PAHs) and heavy metals, their spatial and seasonal distributions, and the factors affecting the variations in concentrations were investigated. The annual average concentration of benzo[a]pyrene was 1.27 ng/m<sup>3</sup>, with a maximum of 10.41 ng/m<sup>3</… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 36 publications
1
7
0
Order By: Relevance
“…e polycyclic aromatic hydrocarbons' content shows obvious seasonal variation and the highest content appears in winter, so they concluded that the factors affecting the concentration of polycyclic aromatic hydrocarbons may have a direct relationship with home heating, fuel combustion in automobile exhaust, and industrial activity in its pollution sources [12]. Ma and others described 16 kinds of PAHs and 16 kinds of nitropolycyclic aromatic hydrocarbons (NPAHs) combined with inhalable particles in cold areas of China and analyzed their sources and health risks.…”
Section: Atmospheric Pollutionmentioning
confidence: 99%
“…e polycyclic aromatic hydrocarbons' content shows obvious seasonal variation and the highest content appears in winter, so they concluded that the factors affecting the concentration of polycyclic aromatic hydrocarbons may have a direct relationship with home heating, fuel combustion in automobile exhaust, and industrial activity in its pollution sources [12]. Ma and others described 16 kinds of PAHs and 16 kinds of nitropolycyclic aromatic hydrocarbons (NPAHs) combined with inhalable particles in cold areas of China and analyzed their sources and health risks.…”
Section: Atmospheric Pollutionmentioning
confidence: 99%
“…This is consistent the China Ministry of Environmental Protection, with the soil PAHs of farmland, forest, and grassland reported to exceed the standard by 19.4%, 10.0%, and 10.4%, respectively (MEP, 2020). Intensive urbanization and industrialization increase PAHs in soil through human activities such as coal burning for electricity generation, coking, petroleum re ning, industrial processing, vehicle combustion, and chemical manufacturing (Baek et al, 2020). The high concentrations of Bbf, Phe, and Flt under construction land observed in this study also indicate industrial activity as a source of PAHs.…”
Section: Sources and Diversity Of Soil Pahs Under Different Land-use ...mentioning
confidence: 52%
“…In this study, the concentration of 16 US EPA priority PAHs in PM 2.5 of Xi'an between November 15 and December 23, 2019 (the heating season), were analyzed. It was worth noting that the Acenaphthene (Ace) concentration in Xi'an was significantly higher than that in South Korea, Thailand, or the United States and even higher than that in other regions of China (Baek et al, 2020; Barhoumi et al, 2020; Dejchanchaiwong et al, 2020; Han et al, 2019; Khadhar et al, 2010). However, the other 15 kinds of PAHs have no significant difference as compared with these in other regions in China.…”
Section: Discussionmentioning
confidence: 99%